JS04.6.A The landscape of tumor cell states and spatial organization in H3-K27M mutant diffuse midline glioma across age and location. (5th September 2022) - Liu, I; Jiang, L; Samuelsson, E; Marco Salas, S; Hack, O; Jeong, D; Shaw, M; Englinger, B; LaBelle, J; Ernst, K; Palova, H; Pokorna, P; et al.
Abstract: Background: Histone 3 lysine27-to-methionine mutations (H3-K27M) frequently occur in childhood diffuse midline gliomas (DMGs) of the pons, thalamus and spinal cord, presumed to be driven by the specific spatiotemporal context of these midline locations during postnatal development. While most common in the pons and at mid-childhood ages, the same oncohistone mutation is recurrently detected in adult DMGs and throughout different midline regions. The potential heterogeneity of tumors at different ages and in different anatomical locations of the midline are vastly understudied. Material and Methods: Through dissecting the transcriptomic, epigenomic and spatial architectures of a comprehensive cohort of patient H3-K27M DMGs - spanning the age range from 2-68 years and locations from spinal cord to thalamus - at single cell resolution, we delineate how age- and location-dependent contexts shape glioma cell-intrinsic and -extrinsic features in light of the shared driver mutation. Results: We identify that oligodendrocyte precursor (OPC)-like cells constitute the stem-like compartment in H3-K27M DMGs across all clinico-anatomical groups, however, depending on location, display varying levels of maturity resembling less differentiated pre-OPCs or more mature OPCs further differentiated along the oligodendroglial lineage. We further demonstrate increased mesenchymal cell states in adult tumors, which we link to age-related differences in glioma-associated immune cell compartments. We for the first time resolve the spatial organization of H3-K27M DMG cell types in intact patient tissues, identifying a local niche of the oligodendroglial lineage. Conclusion: Our study provides a powerful resource for rational modeling and therapeutic frameworks taking into account determinants of age and location in this lethal glioma group.